2022
DOI: 10.3390/ijms23148044
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Eucalyptus Heat Shock Transcription Factor Family and Their Transcriptional Analysis under Salt and Temperature Stresses

Abstract: Heat shock transcription factors (HSFs) activate heat shock protein gene expression by binding their promoters in response to heat stress and are considered to be pivotal transcription factors in plants. Eucalyptus is a superior source of fuel and commercial wood. During its growth, high temperature or other abiotic stresses could impact its defense capability and growth. Hsf genes have been cloned and sequenced in many plants, but rarely in Eucalyptus. In this study, we used bioinformatics methods to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, class B5 is absent from all three of the aforementioned plants, suggesting that it is relatively rare. The physicochemical properties of PbHsf proteins vary greatly, but they are all located in the nucleus (Table 1) as found for poplar (Zhao et al 2023) and E. grandis (Yuan et al 2022).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Interestingly, class B5 is absent from all three of the aforementioned plants, suggesting that it is relatively rare. The physicochemical properties of PbHsf proteins vary greatly, but they are all located in the nucleus (Table 1) as found for poplar (Zhao et al 2023) and E. grandis (Yuan et al 2022).…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to annual herbaceous plants, trees are more susceptible to sustained damage from complex natural stresses due to their prolonged life cycle, and their genetic breeding and improvement are very challenging (Borthakur et al 2022). Among five representative EgHsf genes in Eucalyptus grandis, three are upregulated genes and two downregulated at 4 °C and two upregulated and three downregulated genes at 40 °C (Yuan et al 2022). When the seedlings were exposed to 200 mM NaCl, all five EgHsf genes were upregulated after 12 h and 24 h. These results suggest that Hsf genes play key roles in responding to abiotic stresses in woody plants.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Individual homologous genes of one-to-many or many-to-one purity were identified. Among them, seven EjTIFY genes ( EjJAZ16 , EjJAZ13 , EjJAZ15 , EjJAZ14 , EjJAZ9 , EjJAZ8 , and EjJAZ4 ) showed covariant associations among all five representative species, suggesting that these genes in the EjTIFY gene family played a vital role in the evolutionary process [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Through collinearity analysis, it was found that there are one pair, four pairs, and six pairs of FAR collinear gene pairs between rice and tomato, barley and B. distachyon, respectively, but there was no FAR collinearity between rice and Arabidopsis (Figure 5B). Meanwhile, we found that OsFAR4 exhibited collinearity in several representative species, except Arabidopsis, suggesting that OsFAR4 is more conserved and plays an important role in the evolutionary process [31].…”
Section: Analyses Of Chromosomal Distribution and Gene Duplication Of...mentioning
confidence: 93%